Zeitschrift für Rechtssoziologie : The German Journal of Law and Society (De Gruyter Oldenbourg, 1980)
Established in 1980, the Zeitschrift für Rechtssoziologie - The German Journal of Law and Society offers a forum for the academic analysis of law in its societal context and on the relationship between law and society. The Journal publishes contributions from all disciplines as long as the relationship between law and society can be identified as a core theme.